Climate change in the Arctic: using plant functional types in a meta-analysis of field experiments - Dormann, Carsten; Woodin, S.J. (Functional Ecology, 2002)
1. The effects of global climate change are predicted to be strongest in the Arctic. This, as well as the suitability of tundra as a simple model ecosystem, has led to many field experiments investigating consequences of simulated environmental change.2. On the basis of 36 experiments reviewed here, minor light attenuation by clouds, small changes in precipitation, and increases in UV-B radiation and atmospheric CO2 concentrations will not affect arctic plants in the short term. However, temperature elevation, increases in nutrient availability and major decreases in light availability will cause an immediate plant-growth response and alter nutrient cycling, possibly creating positive feedbacks on plant biomass. The driver of future change in arctic vegetation is likely to be increased nutrient availability, arising for example from temperature-induced increases in mineralization.3. Arctic plant species differ widely in their response to environmental manipulations. Classification into plant functional types proved largely unsatisfactory for generalization of responses and predictions of effects.4. Nevertheless, a few generalizations and consistent differences between PFTs were detected. Responses to fertilization were the strongest, particularly in grasses. Shrubs and grasses were most responsive to elevated temperature.5. Future studies should focus on interactive effects of environmental factors, investigate long-term responses to manipulations, and incorporate interactions with other trophic levels. With respect to plant functional types, a new approach is advocated, which groups species according to their responses to environmental manipulations.